Urinary Zinc Levels and Nutritional Status in Children with Acyanotic Congenital Heart Disease: A Cross-Sectional Study - Pradhana Putra, Fajar; Hariyanto, Didik; Rachmawati Masnadi, Nice; Dianne Jurnalis, Yusri; Nurdin, Asrawati; Perdana Harmen, Anggia (Jurnal Kesehatan - STIKes Prima Nusantara, 2026)
Background: Acyanotic congenital heart disease (CHD) causes increased metabolic demands and nutrient malabsorption, potentially triggering zinc deficiency. Urinary zinc measurement offers a non-invasive method to assess zinc status. This study evaluates the association between urinary zinc levels and nutritional status in children with acyanotic CHD. Methods: An analytical cross-sectional study involving 50 children aged 2–60 months with echocardiography-confirmed acyanotic CHD was conducted at the Pediatric Cardiology Outpatient Clinic, DR. M. Djamil General Hospital, Padang, from October 2024 to August 2025. Nutritional status was assessed by anthropometry using WHO growth standards (weight-for-height z-scores). Spot urinary zinc levels were measured using a colorimetric zinc assay kit (Elabscience, E-BC-K137-M) with absorbance read at 560 nm. One-way ANOVA and post-hoc tests were used for group comparisons. Results: Malnutrition prevalence reached 62% (undernutrition 32%, severe malnutrition 30%). Hypozincuria (urinary zinc <8 µmol/L) was found in 38% of subjects. A highly significant difference in urinary zinc levels was observed across nutritional status groups (p<0.001). Urinary zinc was highest in the well-nourished group (9.6±1.2 µmol/L), followed by undernutrition (8.4±1.8 µmol/L), and lowest in severe malnutrition (6.1±1.5 µmol/L). Post-hoc analysis confirmed significant differences between well-nourished and severely malnourished (p<0.001), and between undernutrition and severe malnutrition (p<0.001). Conclusion: Urinary zinc levels are significantly associated with nutritional status in children with acyanotic CHD, particularly in those with severe malnutrition. Urinary zinc assessment may serve as a practical screening tool to identify zinc deficiency in this population and guide targeted nutritional interventions.